2017
DOI: 10.1371/journal.pone.0183192
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of tinnitus in patients with chronic kidney disease: A nationwide, population-based cohort study

Abstract: Tinnitus mostly results from central and peripheral auditory pathology. Chronic kidney disease (CKD) is a major risk factor for cerebrovascular disease. However, no studies have evaluated the association between tinnitus and CKD. The aim of this study is to investigate the risk of tinnitus in patients with CKD. This retrospective cohort study was conducted using Taiwan National Health Insurance Research Database from 2000 to 2010. We established a CKD group (n = 185,430) and a non-CKD comparison group (n = 556… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 37 publications
(41 reference statements)
2
27
1
6
Order By: Relevance
“…It was mainly diagnosed in long-lasting CKD patients and deteriorated over time [7,8]. It was reported that the highest prevalence of SNHL occurred in individuals with estimated glomerular filtration rate (eGFR) above 45 ml/min/1.73 m 2 [9].…”
Section: Sensorineural Hearing Loss (Snhl)mentioning
confidence: 99%
See 3 more Smart Citations
“…It was mainly diagnosed in long-lasting CKD patients and deteriorated over time [7,8]. It was reported that the highest prevalence of SNHL occurred in individuals with estimated glomerular filtration rate (eGFR) above 45 ml/min/1.73 m 2 [9].…”
Section: Sensorineural Hearing Loss (Snhl)mentioning
confidence: 99%
“…Hearing dysfunction SNHL 28-77% of patients with CKD are affected [7,8] It might result from several structural and functional similarities in kidney and in inner ear, as well as similar antigenicity [8] Potential mechanisms leading to SNHL in CKD Electrolyte disturbances [6] Elevated serum urea and creatinine levels [6] Treatment (ototoxic drugs: aminoglycosides and furosemide, HD itself and prolonged treatment duration) [6,8] Coexisting hypertension or DM [6] Vitamin D deficiency and reduction of Na+ K+ activated ATPase [8] Endolymphatic edema [8] Uremia-induced dysfunctions in nervous system, called "uremic neuropathy" leading to auditory nerve and hearing pathway alterations [8] Formation of amyloid collections in the cochlea induced by permanent HD [8] Toxic influence of aluminum on inner ear [8] SNHL in CKD is usually bilateral and mainly affects high frequencies [8] Speech discrimination seems not to be affected in these patients [8] DPOAE are reduced or absent, and might detect subclinical cochlear dysfunction in CKD [10] ABR tests might reveal lower neural auditory conduction defined by prolongation of ABR waves [11] ABR test might be improved after HD sessions (potentially because of Ca++ ions and urea changes after HD), nevertheless hearing never return to normal [11] SSNHL 1.57-times higher than in GP [12] Mechanism is unknown Worse prognosis of recovery than in non-CKD patients while undergoing systemic steroid therapy for SSNHL [12] Promising treatment results after intratympanic steroid injections in these patients [12] Tinnitus 3.02-times higher in CKD than in GP [9] 4.586-higher in CKD on HD than in GP [9] Mechanism is unclear…”
Section: Additional Informationmentioning
confidence: 99%
See 2 more Smart Citations
“…6 Tinnitus can be accompanied by otological, metabolic, orthopedic, cardiovascular, neurological, dental, and pharmacological conditions. 9 Currently, the treatment methods for tinnitus mainly include counseling, tinnitus maskers, cognitive behavioral therapy, and hearing aids to reduce the distress associated with tinnitus. 7 Despite in Chinese medicine, kidney disease is considered to be associated with tinnitus, 8 the relationship between tinnitus and kidney diseases is rarely reported in modern medicine.…”
Section: Introductionmentioning
confidence: 99%